DESAIN SIMULASI UNJUK KERJA KODE SMALL KASAMI PADA KANAL MULTIPATH FADING - Adi Wiguna Sanjaya, I Kadek; Pramaita, Nyoman; Oka Widyantara, I Made (Jurnal SPEKTRUM, 2021)
Telecommunication capable of handling interference, fading and no less important issues regarding the confidentiality of user information is very much needed in the current technological era, to overcome this spread spectrum technology is quite developed in the advancement of telecommunication technology. In this study, the small kasami code was used as the spreading code. The purpose of this study is to determine the performance of the small kasami code with changes in the number of multipath components using multipath fading channels. The modulation technique uses digital modulation, namely binary phase shift keying (BPSK) with a small kasami code with a code length of 15 in the spreading and spreading process. Analyzed based on BER (Bit Error Rate) versus EB/No (Energy Bit per Noise). In the simulation of flat fading performance using 1 multipath component, flat fading serves as an ideal reference where the simulation BER should resemble the theoretical BER as simulation validation so that it can be used on selective fading channels. Variation of multipath components in frequency selective fading channel produces different BER because there is interference of multipath signal to the desired signal. The number of multipath components as many as 11 have the most interference signals resulting in the worst performance. The value of cross correlation between users has poor performance, where the correlation value of user 1 with 2, 3, and 4 is more than 0, this value shows that many signal levels experience interference between users.